Analysis of Frontier’s Internet Network Quality - Maya Sari; Irwan Sembiring; Hindriyanto Dwi Purnomo (Jurnal Bumigora Information Technology (BITe), 2022)
The demands of internet networks are ever increasing. This is caused by a huge number of applications that use the internet as their basic service and more affordable equipment that can connect to the internet. These conditions are raising a way to measure the quality of network services to see how well it could serve its user, especially regarding the internet. In this study, the parameters used to determine QoS (Quality of Service) are throughput, packet loss, delay and Jitter. Locations of measurement are wired and internet networks at the selected institute which is the shanti buana institute, bengkayang regency. The measurement method used is Quality of Service (QoS). This method is applied when analyzing the quality of the internet network. The results are very satisfactory, while the result of throughput methods are85.95 Mbps, and the amount of packet loss has a very small percentage, namely 1%. The amount of delay obtained is 46,741 ms, while the Jitter is 42,716 ms.